2008
DOI: 10.1002/mar.20207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple language product descriptions on product evaluations

Abstract: This study investigates the influence of bilingual product packaging descriptions on product evaluation. In an experimental study, the evaluation of a product with an English-only package is compared to the evaluation of the same product in a bilingual package. The evaluation of the product in the bilingual package is found to be significantly lower. Ethnocentrism and prejudice are investigated as possible explanations for this differential. The effect of the method of information processing used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In an extension of the debate on information overload, researchers found that the perception of variety is not just a function of the number of options or attributes but also depends on structural factors such as the (dis)organization of the assortment, the number and distribution of attribute levels, the correlation between attributes, and the similarity between options (Fasolo et al, 2006;Gopinath & Glassman, 2008;Hoch, Bradlow, & Wansink, 1999;Kahn & Lehmann, 1991;Kahn & Wansink, 2004;Lee & Lee, 2004;Lurie, 2002Lurie, , 2004van Herpen & Pieters, 2002). Other researchers found that beyond just influencing perception, these structural aspects also affect the ease with which relevant information can be retrieved, which in turn affects the quality of the decision (Lee & Lee, 2004) and the motivation to make a choice (Gourville & Soman, 2005;Russo, 1977).…”
Section: Assortment Structurementioning
confidence: 99%
“…In an extension of the debate on information overload, researchers found that the perception of variety is not just a function of the number of options or attributes but also depends on structural factors such as the (dis)organization of the assortment, the number and distribution of attribute levels, the correlation between attributes, and the similarity between options (Fasolo et al, 2006;Gopinath & Glassman, 2008;Hoch, Bradlow, & Wansink, 1999;Kahn & Lehmann, 1991;Kahn & Wansink, 2004;Lee & Lee, 2004;Lurie, 2002Lurie, , 2004van Herpen & Pieters, 2002). Other researchers found that beyond just influencing perception, these structural aspects also affect the ease with which relevant information can be retrieved, which in turn affects the quality of the decision (Lee & Lee, 2004) and the motivation to make a choice (Gourville & Soman, 2005;Russo, 1977).…”
Section: Assortment Structurementioning
confidence: 99%
“…Despite the appearance of some recent investigations of issues such as the effects of bilingual wording on packages (Gopinath & Glassman, 2008), attention to this important marketing variable continues to lag dramatically behind the level of inquiry devoted to other marketing communication mechanisms such as advertising.…”
Section: General Discussion and Implicationsmentioning
confidence: 99%
“…However, consumers generally have limited information about the country of origin of a brand. Gopinath and Glassman (2008) suggested that it would be worthwhile to examine whether consumers form perceptions of a product's country of origin on the basis of the languages found on the packaging. Language is commonly associated with a country of origin.…”
Section: Visual Cuesmentioning
confidence: 99%